IL-17A Is Critical for CD8+ T Effector Response in Airway Epithelial Injury After Transplantation. Issue 12 (December 2018) - Zhang, Ruochan; Fang, Huihui; Chen, Rongjuan; Ochando, Jordi C.; Ding, Yaozhong; Xu, Jiangnan
Abstract : Background: Airway epithelium is the primary target of trachea and lung transplant rejection, the degree of epithelial injury is closely correlated with obliterative bronchiolitis development. In this study, we investigated the cellular and molecular mechanisms of IL-17A-mediated airway epithelial injury after transplantation. Methods: Murine orthotopic allogeneic trachea or lung transplants were implemented in wild type or RORγt −/− mice. Recipients received anti-IL-17A or anti-IFNγ for cytokine neutralization, anti-CD8 for CD8 + T-cell depletion, or STAT3 inhibitor to suppress type 17 CD4+ /CD8+ T cell development. Airway injury and graft inflammatory cell infiltration were examined by histopathology and immunohistochemistry. Gene expression of IL-17A, IFNγ, perforin, granzyme B, and chemokines in grafts was quantitated by real-time RT-PCR. Results: IL-17A and IFNγ were rapidly expressed and associated with epithelial injury and CD8 + T-cell accumulation after allotransplantation. Depletion of CD8 + T cells prevented airway epithelial injury. Neutralization of IL-17A or devoid of IL-17A production by RORγt deficiency improved airway epithelial integrity of the trachea allografts. Anti–IL-17A reduced the expression of CXCL9, CXCL10, CXCL11, and CCL20, and abolished CD8 + T-cell accumulation in the trachea allografts. Inhibition of STAT3 activation significantly reduced IL-17A expression in both trachea and lung allografts; however, it increased IFNγ expression and cytotoxic activities, which resulted in the failure of airway protection. Conclusions: Our data reveal the critical role of IL-17A in mediating CD8 + T effector response that causes airway epithelial injury and lung allograft rejection, and indicate that inhibition of STAT3 signals could drive CD8 + T cells from Tc17 toward Tc1 development. Abstract : Using murine orthotopic allogeneic trachea or lung transplants, Zhang et al demonstrate critical roles for ROR γt, IL-17 and CD8+ T cells in mediating airway epithelial injury and lung allograft rejection.